Defining the role of neutrophils in the lung during infection: Implications for tuberculosis disease - Gaffney, E.; Murphy, D.; Walsh, A.; Connolly, S.; Basdeo, S. A.; Keane, J.; Phelan, J. J. (Frontiers in Immunology, 2022)
Neutrophils are implicated in the pathogenesis of many diseases involving inflammation. Neutrophils are also critical to host defence and have a key role in the innate immune response to infection. Despite their efficiencies against a wide range of pathogens however, their ability to contain and combat Mycobacterium tuberculosis (Mtb) in the lung remains uncertain and contentious. The host response to Mtb infection is very complex, involving the secretion of various cytokines and chemokines from a wide variety of immune cells, including neutrophils, macrophages, monocytes, T cells, B cells, NK cells and dendritic cells. Considering the contributing role neutrophils play in the advancement of many diseases, understanding how an inflammatory microenvironment affects neutrophils, and how neutrophils interact with other immune cells, particularly in the context of the infected lung, may aid the design of immunomodulatory therapies. In the current review, we provide a brief overview of the mechanisms that underpin pathogen clearance by neutrophils and discuss their role in the context of Mtb and non-Mtb infection. Next, we examine the current evidence demonstrating how neutrophils interact with a range of human and non-human immune cells and how these interactions can differentially prime, activate and alter a repertoire of neutrophil effector functions. Furthermore, we discuss the metabolic pathways employed by neutrophils in modulating their response to activation, pathogen stimulation and infection. To conclude, we highlight knowledge gaps in the field and discuss plausible novel drug treatments that target host neutrophil metabolism and function which could hold therapeutic potential for people suffering from respiratory infections.